Human-Centered Methods to Inform the Design of Information Technologies for Team-based Depression Care - Suh, Jina; Williams, Spencer; Fann, Jesse R.; Fogarty, James; Hsieh, Gary; Bauer, Amy M. (AMIA Clinical Informatics Conference, 2020)
Integrating team-based depression care into cancer services is effective in improving patient outcomes. Technology has a potential to enhance the implementation of such evidence-based depression care, but traditional methods of designing health information technologies (HITs) are insufficient in team-based and complex clinical contexts. We demonstrate the benefits of combining interviews and contextual inquiries to understand various care contexts and perspectives which are applicable to HIT design to support a wide range of chronic disease care.